2006
DOI: 10.1111/j.1745-7254.2006.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Difference in oral absorption of ginsenoside Rg1 between in vitro and in vivo models

Abstract: Aim: To clarify the cause of poor oral absorption of ginsenoside Rg 1 (Rg 1 ), the active ingredient in Panax notoginseng saponins (PNS) used for treating hemorrhage. Methods: Caco-2 cell monolayers were used as an in vitro model to study the transport mechanism of Rg 1 across the intestinal mucosa. Moreover, the serum concentration-time profiles after peroral (po), intraduodenal (id), portal venous (pv) and tail venous (iv) administration of Rg 1 in rats were compared to evaluate the first-pass effects in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 12 publications
4
55
1
Order By: Relevance
“…MMP-3 expression in the joints of the CIA mice was also reduced substantially by the administration of RGSE. Despite low oral absorption and bioavailability of Rg3 and other ginsenosides [31][32][33] , RGSE at 10 mg/kg was concluded to possess a potent anti-arthritic activity, decreasing inflammation in synovial tissues and blocking the destruction of cartilage and bone via the expression of MMP-3. Rg3, rather than other ginsenosides, may contribute to anti-arthritic activity of RGSE.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-3 expression in the joints of the CIA mice was also reduced substantially by the administration of RGSE. Despite low oral absorption and bioavailability of Rg3 and other ginsenosides [31][32][33] , RGSE at 10 mg/kg was concluded to possess a potent anti-arthritic activity, decreasing inflammation in synovial tissues and blocking the destruction of cartilage and bone via the expression of MMP-3. Rg3, rather than other ginsenosides, may contribute to anti-arthritic activity of RGSE.…”
Section: Discussionmentioning
confidence: 99%
“…However, this contradicted the results of a previous study by Lai et al [85], which investigated the pharmacokinetic parameters and bioavailability of G-Rh1 using intravenous and intragastrical administrations in Sprague-Dawley rats. They found that this compound exhibited extremely poor absolute bioavailability of about 1 % and rapid clearance with a short elimination half-life as can be seen in other protopanaxatriol ginsenosides [86]. The phenomenon might be partly explained by its main metabolic pathways, including CYP450-catalyzed mono-oxygenation, the intestinal bacteria mediated deglucosylation, and the gastric acid mediated hydration reaction [85].…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative release of free Sal B and Rg 1 decreased at 6 hours and 8 hours, respectively, which may be due to their own degradation. 34,35 Nanoparticle formulations exhibited a biphasic pattern of drug release for Sal B, R 1 , Rg 1 , and Rb 1 : burst release and sustained release. An initial burst release may be attributed to the immediate release of the surface-associated drug, and a prolonged release in the later stage is due to the slow diffusion of drug from the matrix.…”
Section: In Vitro Drug Release Of Plga Npsmentioning
confidence: 99%